The kingdom of ohio eaudiobook A novel. - Flaming, Matthew (Tantor Media, 2010)
After discovering an old photograph, an elderly antiques dealer living in present-day Los Angeles is forced to revisit the history he has struggled to deny. The photograph depicts a man and a woman. The man is Peter Force, a young frontier adventurer who comes to New York City in 1901 and quickly lands a job digging the first subway tunnels beneath the metropolis. The woman is Cheri-Anne Toledo, a beautiful mathematical prodigy whose memories appear to come from another world. They meet seemingly by chance, and Peter initially dismisses her as crazy. But as they are drawn into a tangle of overlapping intrigues, Peter must reexamine Cheri-Anne's fantastic story. Could it be that she is telling the truth and that she has stumbled onto the most dangerous secret imaginable: the key to traveling through time? Set against the mazelike streets of New York at the dawn of the mechanical age, Peter and Cheri-Anne find themselves wrestling with the nature of history, technology, and the unfolding of time itself.